Plant factories: Reducing energy demand at high internal heat loads through façade design. (15th March 2020) - Graamans, Luuk; Tenpierik, Martin; van den Dobbelsteen, Andy; Stanghellini, Cecilia
Highlights: We investigate the façade's impact on energy and electricity use in plant factories. Lower insulation can reduce cooling demand by 18.8–30.4% through heat dissipation. Optimised opaque façades can reduce electricity use for plant factories by 0.3–2.3% Transparent façades can reduce electricity use for plant factories by 7.4–9.4% We index fundamental strategies for façade construction at high internal heat loads. Abstract: The increase in global food demand has led to the introduction of new food production systems. One key example is the plant factory. Plant factories face the same challenge as many high-tech building functions: high energy demands resulting from high internal heat loads. In this study we investigate how this energy demand can be reduced through façade design. Energy efficient design closely follows function, façade construction and local climate. Therefore, we analysed the effects of façade properties on the energy use in plant factories for three disparate climate zones: Sweden (Dfc), the Netherlands (Cfb) and the United Arab Emirates (BWh). We coupled the building energy simulation program EnergyPlus with a crop transpiration model to calculate the lighting, sensible cooling, latent cooling, and heating demand from the energy balance. In terms of energy demand (kWh m −2 ), opaque façades with high U-values and optimised albedo can reduce the facilities' cooling demand by 18.8%, 30.0% and 30.4%, and their energy demand by 6.1%, 12.5% and 9.5%, for the United Arab Emirates, the Netherlands and Sweden, respectively. In terms of electricity use (kWhe m −2 ), transparent façades are more efficient, as they allow the use of freely available solar energy instead of artificial light. These façades can reduce electricity use by 9.4%, 7.6% and 7.4%, for the United Arab Emirates, the Netherlands and Sweden, respectively. The presented façade design strategies can significantly reduce energy demand in plant factories. The investigation provides a foundation for the energy efficient design of high-tech buildings, tailored to local climate.